Penerapan Metode Prototyping dalam Pengembangan Sistem Audit Internal Tingkat Program Studi (Studi Kasus: Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Lampung) - Gofariyanti Dharmaningtyas; Tristiyanto (Jurnal Pepadun, 2022)
PerBAN-PT No. 5 concerning APS Instruments, Accreditation is an assessment activity to determine the eligibility of a Study Program. The purpose of accreditation is to be able to determine the eligibility of a Study Program based on criteria that refer to the National Higher Education Standards and to guarantee the quality of the Study Program externally both in the academic and non-academic fields. Accreditation status is a benchmark for the performance of the study program concerned and describes the quality, efficiency, and relevance of an organized study program. The person in charge of assessing is called an auditor, the auditor needs information about the study program obtained from completing the accreditation assessment instrument by first making a study program self-evaluation document. In practice, staff must collect data along with evidence to the auditor to carry out an assessment in accordance with the standards set by BAN-PT, but study program staff in data collection still often experience data being scattered from one another, because the data collected is not small. This also sometimes results in less than optimal data collection to the auditor so that it can reduce the assessment. This problem can be overcome by making an Audit Information System so that data collection can be more organized. This information system was built using the prototype method with three stages, namely Listen to Customer, Build/Revise Mock Up, and Test Drive Mock-Up. This system uses the Laravel framework while for coding this system uses the PHP programming language. The testing method used is the Black Box Testing method with the Equivalence Partitioning type. The result of this study is a Web-Based Internal Audit Information System that can facilitate the internal auditing of a study program.